Analisis Peranan Sistem Informasi Akuntansi Pembelian Tunai Dan Penjualan Tunai Dalam Pengendalian Persediaan Barang Dagang Pada Toko Salah Parkir Metro - Saputra, Andri; Nusantoro, Jawoto; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2023)
This type of research is field research with a qualitative descriptive approach. The data collection tools in this study are observation, interviews and documentation. The data analysis technique is through the process of data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the implementation of an accounting information system for cash purchases and cash sales at the Metro Salah Parkir Stores is already computerized. This can be seen from the elements of cash purchases at Metro Salah Parkir Stores, namely: Related functions are the Purchasing Function and Receiving Function, Warehouse Function and Accounting Function. The role of the accounting information system for cash purchases and cash sales in controlling merchandise inventory at the Metro Salah Parkir Stores is in accordance with the internal control components. But there are still a number of problems including excess or shortage between the goods ordered and the goods that have been sent to the Metro Salah Parkir Stores.